Isolation of basic myotoxins from Bothrops Moojeni and Bothrops Atrox snake venoms - Lomonte, Bruno (1990)
Three myotoxins, one from the venom of Bothrops atrox and two from the venom of B. moojeni, were isolated by ion-exchange chromatography on CM-Sephadex C-25. The three toxins are basic proteins with an estimated mol. wt of about 13,500, and similar amino acid compositions. When injected into the gastrocnemius muscle of mice, the three toxins induce drastic myonecrosis of rapid onset, as judged by histological observation and quantitation of plasma creatine kinase levels. B. atrox myotoxin also has phospholipase A2 and anticoagulant activities, whereas B. moojeni myotoxins I and II lack these effects. The three toxins are antigenically similar to each other, and to previously isolated myotoxins I and II from the venom of B. asper, when tested by gel immunodiffusion against rabbit antiserum to B. asper myotoxin I. Two monoclonal antibodies against B. asper myotoxins were tested against the newly purified proteins. MAb-3 recognizes all of them, whereas MAb-4 recognizes only B. atrox myotoxin, by enzyme-immunoassay. B. atrox and B. moojeni myotoxins can be tentatively classified within a group of myotoxins having phospholipase A2 structure present in Bothrops venoms.